STUDI POTENSI TEMPAT PEMBUANGAN AKHIR (TPA) SAMPAH “PUTRI CEMPO” SURAKARTA SEBAGAI SUMBER PAKAN SAPI POTONG - Sudiyono Sudiyono; Eka Handayanta (Caraka Tani: Journal of Sustainable Agriculture, 2010)
This Research aim to to know the potency from place of exile final garbage Putri Cempo Surakarta as feed source of beef cattle. Research executed during six-month at some locations, there are: 1) TPA Garbage " Putri Cempo" Mojosongo Surakarta, for the intake of sampel garbage 2) Biochemical and Nutrition Laboratory,Faculty of Animal Husbandry UGM to analyse proximat of feed organic garbage 3). Laboratory of BBVET, Wates Yogyakarta for the analysis of content heavy metal ( Pb and Hg) on organic garbage. Result of intake sample garbage thrown to TPA " Putri Cempo" and dissociated by organic garbage and inorganic garbage, showed that amount of organic garbage much more many than inorganic. Amount of organicmatter of garbage from each the source of garbage thrown in TPA, among others garbage domestic was 63,82%, market garbage was 83,21% and public garbage 67,53%. Result analyse the proksimat seen [by] that protein content ( organic PK) Garbage range from 10,00 - 12,79%. and dry matter (DM) 26,88-34,01 %. Pursuant to its the dry matter content, hence totalizeing organic BK garbage during five the last year ware range from 15,81 - 16,56 thousand ton / year, if assumed by beef cattle potencially which fattening with the body wight 300 kg/head, go with the tide and ability consume feed ( in DM) equal to 3% body wight ( 9 Kg/head/day or 3.285 kg/head/year) hence the organicmatter of garbage can answered the demand of 4812 - 5041 head of beef cattle. The garbage was conttent of heavy metal of lead (Pb) from organic garbage, but the trace content of mercury (Hg)